DECISIVE MOMENT IN PERFORMING ART PHOTOGRAPHY: BETWEEN AESTHETIC SENSE AND CREATIVE PRACTICE - Jauhari, Jauhari; Marianto, M. Dwi; Irwandi, Irwandi (ISI Press Institut Seni Indonesia Surakarta, 2025)
This creative research investigates photographic artworks by referring to Henri Cartier-Bresson's concept of the Decisive Moment. This artistic research aims to create a body of performing arts photography that transcends mere documentation, offering both aesthetic and reflective significance to spontaneously occurring sublime moments. The employed methodology is artistic research characterized by a conceptual framework, visual exploration, and art practices. The resultant work comprises a collection of documented photographs of dance performances captured during the World Dance Day event at Teater Besar ISI Surakarta, Taman Budaya Jawa Tengah, and Pura Mangkunegaran, which encapsulate peak emotional moments, body gestures, and the interplay of space and light, both intuitively and reflectively. This study is grounded in Gilles Deleuze's theory of sublime situations and M. Dwi Marianto's aesthetic insights, which inform the interpretation of artistic moments. The study's findings suggest that the Decisive Moment approach can enhance the documentation of the performing arts by providing a more deeper layer of visual interpretation. This research recommends an in-depth exploration of the interplay between artistic intuition and aesthetic awareness in the creation of performing arts photography.